AN APPRAISAL OF WHISTLE BLOWING ACT AND ITS IMPLICATIONS USING OPINIONS OF JOURNALIST IN RIVERS STATE - Ordu, Nnendah Chigwuyari; Barigbon , G. Nsereka; Whyte, Dike Harcourt; Itieke-Idamieba, Harry (International Research Journal of Arts and Communication, 2025)
The study evaluates the application of whistle blowing Act and it's implications using opinions of Journalist in Rivers State. To achieve this, the study raised three objectives, amongst others were to; analyze the effectiveness of the Whistleblowing Act in promoting transparency and accountability in Rivers State, Nigeria; assess the role of journalists in Rivers State in reporting and disseminating information related to whistleblowing and corruption. This study was anchored on two theories; the ethical theory and communication accommodation theory. The study adopted the survey research design, the population of this study comprised of all the registered journalists in Rivers State. Therefore, the total population of the study is 485. Taro Yamane sample size determination formula was used to arrive at the sample size of 228. Purposive sampling technique was used to administer the instrument to the respondents. Questionnaire was used as the instrument for data gathering and data was analyzed using Weighted Mean Scores (four point Likert Scale). Findings of this study revealed that Whistleblowing Act impacts greatly in reducing corruption and in ensuring accountability when effectively implemented. Findings of this study showed that journalist have a lot of role to play in advocating for effective implementation of the Whistleblowing Act. The study concluded that Whistleblowing Act impacts greatly in reducing corruption and in ensuring accountability when effectively implemented. The study also concluded that journalist have a lot of role to play in advocating for effective implementation of the Whistleblowing Act. The study recommended that to enhance transparency and accountability, the government of Rivers State should establish mechanisms for robust enforcement of the Whistleblowing Act. This includes creating secure, accessible platforms for reporting and ensuring comprehensive protection for whistleblowers to mitigate fear of retaliation. The study also recommended that journalists in Rivers State should be equipped with specialized training on investigative reporting, whistleblowing processes, and ethical reporting standards. This will enable them to effectively uncover and disseminate information on corruption while safeguarding the integrity of whistleblowers and their reports